Surface plasmon resonance based sensor using one-dimensional photonic crystal - Muhammad Kamran; Chuxian Qin (Results in Optics, 2023)
A surface plasmon resonance (SPR) based sensor is presented for the optical sensing that employs one-dimensional photonic crystal (1DPC). An interface of a metal and 1DPC is utilized to excite the surface plasmon-polariton (SPP) waves using prism-coupling. The 1DPC is made up of a bilayer structure of two different dielectric materials. The excited SPP waves are utilized to sense a small change in the refractive index of the dielectric material. A very simple and compact design is proposed for the optical sensing of the dielectric material. A p-polarized plane wave is incident from the metal side and the change in the refractive index of the dielectric material is observed by computing the corresponding change in the incidence angle of excitation of the SPP wave. Absorptance peaks are shifting with a small change in the refractive index of the dielectric materials. It is observed that by changing the refractive index of the prism sensitivity changes with an inverse relation. The power density of the proposed sensor is limited to the metal and 1DPC interface which is the manifestation of the excitation of the SPP wave at that interface. Better results of sensitivity are achieved using this simple design of metal and 1DPC.